(untitled) (I libri digitali di XY, 2020)
Preface. In the shade of the Torrione d’Augusto. Adalberto Libera in Trento, words and syntax Fabio Campolongo Introduction Piazza Venezia, Largo Porta Nuova and Via Galilei in the redesign of the city of Trento during fascism The contribution of the National Institute of Insurance to the development of architecture in Italy between the two Wars. The case of Bozen Adalberto Libera and Trento. Trentino projects of the 1930s Adalberto Libera and research on the theme of living in the 1930s and 1940s Adalberto Libera’s first projects for the INA building in Trento (1938–43) The edification (1946–50) The INA building and the new face of Largo Porta Nuova and Piazza Venezia in the 1950s Afterword. Adalberto Libera 1903 – 1963 Marco Mulazzani Annotated references and documentary sources Adalberto Libera’s projects for the INA building: graphic reconstructions Cristina Pellegatta The INA building in Paolo Sandri’s photographs (2018) English texts. Introduction and chapters abstracts